Participation of mitochondrial permeability transition pore in the effects of ischemic preconditioning in hypertrophied hearts: Role of NO and mitoKATP - Fantinelli, Juliana Catalina (2013)
Background: The mitochondrial permeability transition pore (mPTP) plays an important role in ischemia–reperfusion in normotensive animals. Our study aims to define their participation in the ischemic preconditioning (IP) in hypertrophied hearts and to assess the role played by NO and mitochondrial ATP-dependent K channels (mitoKATP). Material and methods: Isolated hearts from spontaneously hypertensive rats (SHR) and age-matched normotensive rats Wistar Kyoto (WKY) were subjected to 35-min or 50-min global ischemia (GI) followed by 2-hour reperfusion (R). IP was induced by a single cycle of 5-min GI and 10-min R (IP1) or three cycles of 2-min GI and 5-min R (IP3) applied before to prolonged ischemia. L-NAME (NOS inhibitor) or 5-HD (mitoKATP blocker) to investigate the role played by NO and mitoKATP, respectively were administered. Infarct size (IS), myocardial function, reduced glutathione (GSH) — as marker of oxidative stress and MnSOD cytosolic activity — as an index of mPTP opening were determined. Results: IP1 significantly decreased the IS in WKY hearts at both ischemia duration times. In SHR, IP1 decreased the IS observed in GI35 but it did not modify that detected at 50-min GI, which was limited by IP3. IP preserved GSH content and decreased MnSOD cytosolic activity in both rat strains. These protective effects were annulled by L-NAME and 5-HD for both ischemic periods in SHR, whereas in WKY they were only effective for 50-min GI. Conclusion: Our data demonstrate that the cardioprotection achieved by ischemic preconditioning in hearts from SHR hearts involves an attenuation of mPTP opening NO and mitoKATP-mediated.